Students' Perception on The Use of The Bingo Game as a Gamification - Artika Wina Fitriani; Gigih Ariastuti Purwandari; Actinis Muqsitha Paradista (Haumeni Journal of Education, 2025)
Conventional teaching techniques frequently result in a dull and uninteresting learning environment. The bingo game has proven to be one of the most useful and adaptable gamified teaching strategies available to educators. It may transform traditional learning exercises into dynamic experiences. This research explored students' perceptions on the use of the bingo game as a gamification at Madyathika Polytechnic. This research used a descriptive quantitative approach. The research involved 40 participants consist of the first semester students of the Madyathika Polytechnic. The data were collected through pre-test and post-test, questionnaires, observation and interviews. They were analyzed using the quantitative methods approach. The result of the research indicated that the paired samples t-test revealed a significant difference between pre-test and post-test scores (p < 0.001), indicating that the bingo game effectively improved participants' scores, with a mean post-test score of 48.5 compared to a mean pre-test score of 30.8. In addition, a significant majority of respondents (75%) found the bingo game helpful for understanding the material. Additionally, 85% reported a vibrant classroom atmosphere, and 75% noted clear instructions. Overall, it is recognized as a successful educational tool promoting quick thinking through gamification.